NGHIÊN CỨU CHẾ TẠO VIÊN XỬ LÝ NƯỚC TRONG TÌNH HUỐNG KHẨN CẤP - Nguyễn, Trường Giang; Ngô, Cao Cường; Đỗ, Tất Thịnh; Nguyễn, Trọng Dân (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH MANUFACTURING WATER TREATMENT TABLETS IN EMERGENCYIn this study, a tablet for emergency water treatment was fabricated, with components: coagulant-precipitant (aluminum sulfate), pH regulator (sodium bicarbonat), primary colloidal flocculant (carboxylmethyl cellulose), secondary colloidal flocculant (cationic polyacrylamide), agglomeration matrix (microcrystalline cellulose), adsorbent of heavy metal ions and pesticide content (zeolite), disinfectant-sanitizer (sodium dichlorisocyanurate), each tablet weighs about 570 - 590 mg, treating for 1 liter of river or lake water. Water after treatment meets National technical regulation on drinking water quality - QCVN 01:2009/BYT, which is issued by Ministry of Public Health, Vietnam.